FEATURES OF MANAGEMENT TACTICS IN PREGNANT WOMEN WITH CERVICAL PATHOLOGY - Agababyan, L.R.; Rabbimova, N.U. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2025)
Introduction. The aim of this study was to optimize the management tactics in pregnant women with cervical pathology through comprehensive clinical-laboratory diagnostics and a personalized therapeutic approach. Materials and Methods. This prospective study included 1000 pregnant women, among whom cervical pathology was diagnosed in 28.4% of cases. Traditional diagnostic methods (Pap smear) were compared with modern techniques (liquid-based cytology, molecular biological methods). The effectiveness of glycyrrhizic acid therapy was also assessed. Results. An evidence-based management algorithm and a clinical software tool were developed for managing cervical pathology during pregnancy. Conclusion. The findings demonstrate a significant advantage of personalized approaches and modern diagnostic methods, contributing to improved perinatal outcomes and a reduction in obstetric complications.